SYNTHESIS OF ACETATE CELLULOSA FROM THE PALM OIL EMPTY FLOOR THROUGH THE REACTION OF ACTIVATION - Mauliana Mauliana; Eka Kurniasih; Syafruddin Syafruddin (Jurnal Sains dan Teknologi Reaksi, 2019)
Acetate cellulose is cellulose whose hydroxyl group is replaced by an acetyl group. Celluloseacetate has a high enough attractiveness because it is biodegradable so it is environmentally friendly. The purpose of this study is to increase the acetyl content of cellulose acetate by theacetylation reaction. This study uses 25 grams of empty fruit bunches to get cellulose, the delignification process is carried out for 30 minutes with NaOH solution, and the bleachingprocess for 1.5 hours with H2O2 solution. Next, as much as 5 grams of cellulose was carriedout by the acetylation process by adding glacial CH3COOH solution, anhydrous CH3COOHsolution with a ratio of 1:10, 1: 12.5 and 1:15 (w / v) and H2SO4 as a catalyst, withtemperature variations of 40oC, 55oC and 70oC. Next, an acetyl concentration was analyzedby titration, and substitution degree analysis was carried out. The best results obtained fromthe two analyzes will be carried out the Fourier Transform Infrared (FTIR) test and theScanning Electron Microscope (SEM) test. Acetyl content obtained was 8,152 - 24,58% andthe degree of substitution obtained was 0,3 - 1,2%.